2000
DOI: 10.1021/jf990773a
|View full text |Cite
|
Sign up to set email alerts
|

The Physicochemical Property of Shark Type I Collagen Gel and Membrane

Abstract: The physicochemical properties of shark type I collagen gel and membrane were not same as those of pig type I collagen. The denaturation temperature of shark collagen gel was about 15 degrees C lower. According to scanning electronic micrography, the diameter of shark collagen fibril was relatively thin and more homogeneous. The breaking strength of shark collagen gel was greater, and shark collagen membrane had a greater mechanical strength and a higher water vapor sorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 16 publications
2
30
0
Order By: Relevance
“…As far as we know, this is the first study about skin collagen from these species, such as rabbit fish (Chimera monstrosa) or small-spotted catshark (S. canicula). Furthermore, it has been previously reported that shark skin collagen provides an unique material for different purposes as biomaterial, in the feed industry, or cell culture (Nomura et al, 2000). Most collagen properties-such as gelling ability, viscosity, or thermal denaturation-depend on their amino and imino acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, this is the first study about skin collagen from these species, such as rabbit fish (Chimera monstrosa) or small-spotted catshark (S. canicula). Furthermore, it has been previously reported that shark skin collagen provides an unique material for different purposes as biomaterial, in the feed industry, or cell culture (Nomura et al, 2000). Most collagen properties-such as gelling ability, viscosity, or thermal denaturation-depend on their amino and imino acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…The original degradation temperature of collagen was only 39 ℃. 29 Thus the grafted collagenAl 2 O 3 /SnO 2 composites possessed good thermal stability. The different changes upon temperature increase indicated the interactions between the grafted collagen-co-nanoparticles and their structures were different from those of the grafted collagen-xerogel, which improved the thermal stability of the grafted collagen.…”
Section: Thermal Analysismentioning
confidence: 91%
“…Their properties were studied by thermal denaturation temperature using differential scanning calorimetry, solubility, and amino acid analysis. Yoshimura et al (2000) and Nomura et al (2000) extracted collagen from the skin of great blue sharks (Prionace glauca) and investigated the physicochemical properties. Also, similar studies were carried out on collagen isolated from the skins of jellyfish and cuttlefish (Nagai et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%